A preliminary examination of an in situ dual dye approach to measuring light fluxes in lotic systems. (12th December 2013) - Minor, Elizabeth C.; James, Elizabeth; Austin, Jay A.; Nelson, Veronica; Lusk, Ryan; Mopper, Kenneth
<x xml:space="preserve">Abstract</x> Light is a critical parameter in aquatic ecosystems, affecting primary production and in situ photochemistry. However, measuring light exposure for suspended particles or dissolved components in a dynamic water column can be challenging with existing Eulerian approaches. Here, we assess the simultaneous deployment of two dyes differing in photolability (rhodamine WT and fluorescein) as a Lagrangian measure of sunlight exposure in a lotic system. Fluorescein is sensitive to light exposure; rhodamine WT is relatively photostable. We examined dye fluorescence at various pH, salinity, and temperature conditions. We also tested dye photolability as a function of pH and wavelength range. In conjunction with this laboratory work, we performed initial field testing of the dual‐dye approach in a stream on the north shore of Lake Superior, USA. Irradiation of the dyes using long‐pass filters identified wavelengths ≥ 420 nm as responsible for the vast majority of the loss of fluorescein fluorescence, with rhodamine appearing relatively photostable in these short‐term studies across the wave‐length ranges tested. Dye response to irradiation is pH‐sensitive; the dual‐dye approach will require additional calibration for acidic or basic waters and should be used with caution in aquatic systems undergoing strong (several pH unit) changes in pH. Field testing showed that the fluorescein to rhodamine WT ratio decreased approximately linearly with light exposure. The dual‐dye methodology shows promise as an in situ light sensor applicable to water column species in lotic systems if temperature is recorded, and the pH range is measured and relatively stable (e.g., varies by < 1 unit).